Influence of disulfide bond isoforms on drug conjugation sites in cysteine-linked IgG2 antibody-drug conjugates. Issue 4 (19th May 2018) - Liu-Shin, Lily; Fung, Adam; Malhotra, Arun; Ratnaswamy, Gayathri
ABSTRACT: Cysteine-linked antibody-drug conjugates (ADCs) produced from IgG2 monoclonal antibodies (mAbs) are more heterogeneous than ADCs generated from IgG1 mAbs, as IgG2 ADCs are composed of a wider distribution of molecules, typically containing 0 – 12 drug-linkers per antibody. The three disulfide isoforms (A, A/B, and B) of IgG2 antibodies confer differences in solvent accessibilities of the interchain disulfides and contribute to the structural heterogeneity of cysteine-linked ADCs. ADCs derived from either IgG2-A or IgG2-B mAbs were compared to better understand the role of disulfide isoforms on attachment sites and distribution of conjugated species. Our characterization of these ADCs demonstrated that the disulfide configuration affects the kinetics of disulfide bond reduction, but has minimal effect on the primary sites of reduction. The IgG2-A mAbs yielded ADCs with higher drug-to-antibody ratios (DARs) due to the easier reduction of its interchain disulfides. However, hinge-region cysteines were the primary conjugation sites for both IgG2-A and IgG2-B mAbs.